The Changing Leadership Roles of »Dedes« in the Alevi Movement: Ethnographic Studies on Alevi Associations in Turkey and Germany from the 1990s to the Present - Cosan Eke, Deniz (transcript, 2021)
What is the function of clerical leadership in Alevism based on sociocultural and political understandings? To answer that complex question, Deniz Cosan Eke examines the political, cultural, and religious debates surrounding Alevis and the Alevi movement in relation to the ideas and claims of the Turkish state, Alevi communities in Turkey, and migrant Alevi communities in Germany. The book, which focuses on the emergence of collective emotions in religious rituals, the struggle of religious groups in migration processes, and the leadership role of clergy in social movements, is of great interest to a wide readership.